Analisis Faktor yang Mempengaruhi Inflasi di Indonesia Periode 1988-2019 dengan Metode Error Correction Model (ECM) - Julla Mufarrikhah (Diponegoro Journal of Economics, 2021)
Inflation is still a problem in itself for the State of Indonesia, where every year it always fluctuates, causing uncertainty for the economy. This studyvaims to determinevthe effect of the money supply, GDP, world oil prices, and exchange rates on inflation in the short.and long term in Indonesia in the period 1988-2019. The methodvused is the error correction model (ECM). The results show that the ECT coefficient value (-1) is -0.8940, which means that short-term fluctuations in balance will be corrected towards long-term equilibrium quickly. Simultaneously, the variables used in this study have a significant effect on inflation. In the short term only GDP has a significant negative effect on inflation in Indonesia, in the long term GDP and the exchange rate have a significantvnegative effect on inflation, while the money supply and world oil prices have no significant effect on inflation in Indonesia.